2021
DOI: 10.3390/foods10050929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Innovative Packaging Materials on Quality Parameters and Aromatic Fingerprint of Extra-Virgin Olive Oils

Abstract: The performance of two innovative packaging materials was investigated on two Sardinian extra-virgin olive oils (Nera di Gonnos and Bosana). In particular, a transparent plastic film loaded with a UV-blocker (packaging B) and a metallized material (packaging C) were compared each other and to brown-amber glass (packaging A). During accelerated shelf-life tests at 40 and 60 °C, the evolution of quality parameters (i.e., acidity, peroxide value, K270, and phenolic content) was monitored, together with the aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Traditional studies on oil storage suggested that oil stored in stainless steel had better qualitative level (with significantly higher levels of phenols and lower values of the oxidative indices) than that stored in transparent clear and green colored glass [ 16 ] and that stainless and dark glass appeared to be the most adequate packaging materials compared to clear PET or clear glass [ 42 ]. However, recent studies suggest other innovative packaging materials with outstanding oxygen barriers (e.g., flexible PET with UV-blocker) can outperform glass in terms of quality parameters [ 14 ], suggesting the need to further explore the impact of new innovative solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditional studies on oil storage suggested that oil stored in stainless steel had better qualitative level (with significantly higher levels of phenols and lower values of the oxidative indices) than that stored in transparent clear and green colored glass [ 16 ] and that stainless and dark glass appeared to be the most adequate packaging materials compared to clear PET or clear glass [ 42 ]. However, recent studies suggest other innovative packaging materials with outstanding oxygen barriers (e.g., flexible PET with UV-blocker) can outperform glass in terms of quality parameters [ 14 ], suggesting the need to further explore the impact of new innovative solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Several packaging materials have been studied for oils from olives, including glass, metals (tin-coated steel) and, more recently, plastics [ 12 ]. The literature provides numerous comparisons between different materials [ 6 , 7 , 10 , 14 , 15 , 16 , 17 ]. Glass is among the most commonly used material for oil packaging [ 8 , 10 ], as it is considered the first choice as an oil container because it is impermeable to water vapor and volatile organic compounds, and it can be given light-filtering properties [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important key factor to address emerging challenges of sustainable food consumption is the reduction of the environmental footprint of packed food. Thus, the performance of two innovative packaging materials in protecting EVOO from oxidation phenomena was investigated by Farris et al [6]. In particular, a transparent plastic film loaded with a UV-blocker and a metallized material were compared to brown-amber glass during accelerated shelf-life tests at 40 and 60 • C. The transparent film emerged as the best-performing material to preserve EVOO quality.…”
mentioning
confidence: 99%